EIB Investment Survey 2022 - EU overview - European Investment Bank (European Investment Bank, 2022)
This unique insight into the corporate investment landscape in the European Union examines companies' finance needs and the constraints they face. The 2022 edition delves into the aftermath of the economic shock produced by the COVID-19 crisis and the readiness of firms to cope with the new massive shocks that are testing corporate resilience. The report assesses how response and recovery programmes put in place by the European Union and by national governments have helped firms, but also shows how firm perceptions of investment conditions are overshadowed again by recent events. In addition, the EIBIS EU overview presents firm reactions to outstanding structural transformation needs and more specifically the extent to which European firms are addressing the need to make their businesses more green and digital. It also highlights how European firms counter sudden shocks, for example by assessing their responsiveness to international trade disruptions. The survey is based on interviews with 12 000 companies across the 27 European Union countries, and it includes a benchmark sample from the United States. This overview provides the aggregated results for the European Union. "